In-hospital acute kidney injury and atrial fibrillation: incidence, risk factors, and outcome - Guoqin Wang; Lijiao Yang; Nan Ye; Weijing Bian; Changsheng Ma; Dong Zhao; Jing Liu; Yongchen Hao; Na Yang; Hong Cheng (Renal Failure, 2021)
Background The incidence and the risk factors of in-hospitalized acute kidney injury (AKI) in patients hospitalized for atrial fibrillation (AF) were unclear. Methods The Improving Care for Cardiovascular Disease in China-AF (CCC-AF) project is an ongoing registry and quality improvement project, with 240 hospitals recruited across China. We selected 4527 patients hospitalized for AF registered in the CCC-AF from January 2015 to January 2019. Patients were divided into the AKI and non-AKI groups according to the changes in serum creatinine levels during hospitalization. Results Among the 4527 patients, the incidence of AKI was 8.0% (361/4527). Multivariate logistic analysis results indicated that the incidence of in-hospital AKI in patients with AF on admission was 2.6 times higher than that in patients with sinus rhythm (OR 2.60, 95% CI 1.77–3.81). Age (per 10-year increase, OR 1.22, 95% CI 1.07–1.38), atrial flutter/atrial tachycardia on admission (OR 2.16, 95% CI 1.12–4.15), diuretics therapy before admission (OR 1.48, 95% CI 1.07–2.04) and baseline hemoglobin (per 20 g/L decrease, OR 1.21, 95% CI 1.10–1.32) were independent risk factors for in-hospital AKI. β blockers therapy given before admission (OR 0.67, 95% CI 0.51–0.87) and non-warfarin therapy during hospitalization (OR 0.71, 95% CI 0.53–0.96) were associated with a decreased risk of in-hospital AKI. After adjustment for confounders, in-hospital AKI was associated with a 34% increase in risk of major adverse cardiovascular (OR 1.34, 95% CI 1.02–1.90, p = 0.023). Conclusions Clinicians should pay attention to the monitoring and prevention of in-hospital AKI to improve the prognosis of patients with AF.